(untitled) (Salam International Academic Journal, 2023)
This study endeavors to rectify a misconception regarding the interpretation of Surah al Ahzab verse (33). Some scholars, who may not fully grasp the nuances of non-explicit or allegorical verses—those verses with multiple meanings and interpretations—tend to separate the first and second parts of the aforementioned verse وَقَرنَ فِي بُيُوتِكُنَّ. In doing so, they often focus solely on the first part and overlook the explanatory nature of the second part, leading to a misinterpretation of this blessed verse. This article aims to briefly address and correct this misunderstanding. The accurate interpretation is that Muslim women are permitted to leave their homes while adhering to the Sharia veil for lawful activities. This interpretation aligns with the consensus of jurists and Hadith scholars, reinforcing the notion that it is incorrect to separate and understand both sentences of the verse independently. Therefore, the correct interpretation of the Quran is the one adopted by the majority of interpreters. The verse can be understood as follows: "O Muslim women! Stay at home, i.e., do not appear as the display of the former times of ignorance." In essence, this verse signifies that Muslim women are not allowed to adopt the immodest practices of the past, but as long as they do not engage in such behaviors, they are permitted to leave their homes for lawful activities. Consequently, this research concludes that depriving a large segment of society of their rights based on an incorrect interpretation of this verse is unjust. However, women who do not observe Islamic etiquette when venturing outside should be advised accordingly.